Vitamin D and calcium supplementation in women undergoing pharmacological management for postmenopausal osteoporosis: a level I of evidence systematic review - Filippo Migliorini; Nicola Maffulli; Giorgia Colarossi; Amelia Filippelli; Michael Memminger; Valeria Conti (European Journal of Medical Research)
Abstract The present systematic review investigates whether different doses of vitamin D and calcium supplementation in women with postmenopausal osteoporosis undergoing antiresorptive therapy have an association with BMD (spine, hip, femur neck), serum markers of osteoporosis (bone-ALP, NTX, CTX), the rate of pathological vertebral and non-vertebral fractures, adverse events, and mortality. This systematic review was conducted according to the PRISMA 2020 guidelines. PubMed, Google Scholar, Embase, and Scopus databases were accessed in September 2024. All randomised clinical trials (RCTs) comparing two or more treatments for postmenopausal osteoporosis supplemented with vitamin D and/or calcium were accessed. Only studies that indicated daily vitamin D and/or calcium supplementation doses were accessed. Data from 37 RCTs (43,397 patients) were retrieved. Patients received a mean of 833.6 ± 224.0 mg and 92.8 ± 228.7 UI of calcium and vitamin D supplementation, respectively. The mean length of the follow-up was 25.8 ± 13.3 months. The mean age of the patients was 66.4 ± 5.6 years, and the mean BMI was 25.2 ± 1.6 kg/m2. There was evidence of a statistically significant negative association between daily vitamin D supplementation and gastrointestinal adverse events (r = − 0.5; P = 0.02) and mortality (r = − 0.7; P = 0.03). No additional statistically significant associations were evidenced. In postmenopausal women who undergo antiresorptive treatment for osteoporosis, vitamin D was associated with a lower frequency of gastrointestinal adverse events and mortality. Calcium supplementation did not evidence an association with any of the endpoints of interest. Level of evidence Level I, systematic review of RCTs.